2006
DOI: 10.1373/clinchem.2006.068502
|View full text |Cite
|
Sign up to set email alerts
|

Automated Chemiluminescence-Immunoassay for Aldosterone during Dynamic Testing: Comparison to Radioimmunoassays with and without Extraction Steps

Abstract: Background: Measurements of aldosterone have become more common since the recognition that primary aldosteronism is a more frequent cause of hypertension than previously believed. Our aim was to compare concentrations reported by 4 assays for samples obtained after saline infusion during dynamic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 20 publications
5
78
0
3
Order By: Relevance
“…Differences in the specificity of antibodies as well as several other factors may contribute, one important issue arising from the difference in calibration of assays which often generates higher values in some compared with lower values in others. Major differences in mean aldosterone values despite high inter-assay correlations are common and have previously been described (Schirpenbach et al 2006). It was our finding that the DPC kit systematically measures samples w30% higher than the assay developed here.…”
Section: Figuresupporting
confidence: 74%
See 1 more Smart Citation
“…Differences in the specificity of antibodies as well as several other factors may contribute, one important issue arising from the difference in calibration of assays which often generates higher values in some compared with lower values in others. Major differences in mean aldosterone values despite high inter-assay correlations are common and have previously been described (Schirpenbach et al 2006). It was our finding that the DPC kit systematically measures samples w30% higher than the assay developed here.…”
Section: Figuresupporting
confidence: 74%
“…Comparison of aldosterone levels before and after chromatographic purification was carried out using partition chromatography with celite as the inert support (Celite 545 AW, SigmaAldrich) according to a modified version of the method described in Abraham et al (1972) and used for comparison of chemiluminescence immunoassay in Materials and Methods in Schirpenbach et al (2006). Briefly, the stationary phase consisted of 30% formamide in water, while the mobile phase consisted of a mixture of ethyl acetate in n-hexane with increasing polarity in a stepwise fashion.…”
Section: Chromatographic Separation Of Aldosterone For Use In Immunoamentioning
confidence: 99%
“…Limitations of the study include the sensitivity of the aldosterone assays, making reproducibility and agreement at low aldosterone concentrations questionable. Such limitations have been reported for plasma aldosterone concentrations before [17], but might be even more important for salivary aldosterone concentrations, which are even lower than those found in plasma. …”
Section: Salivary Aldosterone Profilingmentioning
confidence: 83%
“…Schirpenbach et al (22) clearly demonstrated markedly different results in a comparison of four different aldosterone assays. It is possible in some cases that a poor comparability of laboratory methods (22,23) for the determination of aldosterone and renin activity accounted for non-confirmation of mineralocorticoid hypersecretion. However, it has to be underlined that only one out of the eight cases retested with the same method as at diagnosis had PA confirmed, suggesting that changing of the analytical method was probably not a major problem.…”
Section: Nc-pa (Nz26)mentioning
confidence: 99%